Situation Report: Yugoslavia, 1 March 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Academics Urge a Change in the System / by Zdenko Antic Rejection of "Socialism of the Poor" / by Slobodan Stankovic Rehabilitations Discussed / by Slobodan Stankovic The Role of Labor Unions / by Slobodan Stankovic Elleinstein Gives Interview to Yugoslav Periodical / by Slobodan Stankovic